2022
DOI: 10.3324/haematol.2021.280257
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in addition to LMB-based chemotherapy regimen in children and adolescents with primary mediastinal large B-cell lymphoma: results of the French LMB2001 prospective study

Abstract: Primary Mediastinal large B-cell Lymphoma (PMLBL) is a rare entity predominantly affecting adolescents and young adults. Recently, an international phase 2 trial in pediatric patients using dose-adjusted etoposide, doxorubicin, and cyclophosphamide with vincristine and prednisone plus rituximab (DA-EPOCH-R) failed to reproduce excellent survival reported in some adult studies. The optimal therapy regimen needs to be determined in this disease. French prospective LMB2001 trial included all patients < 18 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The Inter-B-NHL ritux 2010 study reported grade ≥3 infections in 4% of the courses and 17% of the patients compared with 58.6% infections grade ≥3 in other LMB-based chemotherapy trials. The LMB2001 trial included 42 children with primary mediastinal B-cell lymphoma (PMBCL) treated with LMB with or without rituximab, and recorded one case of candidemia (4.8%) in the rituximab arm, but no toxic death [ 30 ]. Strikingly, a study on 88 children with diffuse large B cell lymphoma (DLBCL) that included patients with human immunodeficiency virus (HIV) infection did not observe an increased incidence of infection-related deaths in patients who received rituximab plus chemotherapy compared with those who were treated with chemotherapy alone [ 31 ].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…The Inter-B-NHL ritux 2010 study reported grade ≥3 infections in 4% of the courses and 17% of the patients compared with 58.6% infections grade ≥3 in other LMB-based chemotherapy trials. The LMB2001 trial included 42 children with primary mediastinal B-cell lymphoma (PMBCL) treated with LMB with or without rituximab, and recorded one case of candidemia (4.8%) in the rituximab arm, but no toxic death [ 30 ]. Strikingly, a study on 88 children with diffuse large B cell lymphoma (DLBCL) that included patients with human immunodeficiency virus (HIV) infection did not observe an increased incidence of infection-related deaths in patients who received rituximab plus chemotherapy compared with those who were treated with chemotherapy alone [ 31 ].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…The French LMB2001 prospective study evaluated intensive LMB-based chemotherapy (based on the FAB/ LMB96 protocol) in pediatric patients with PMBL (42 of 773 patients with newly diagnosed B-cell NHL had PMBL). 28 All patients received prephase COP followed by 4 to 8 courses (induction, consolidation, and maintenance) of chemotherapy, and rituximab was added to chemotherapy after 2008. In 2010, the protocol was modified to recommend 6 courses of LMB-modified chemotherapy (B/C) with rituximab for all patients (2 induction courses of R-COPADM followed by 2 consolidation courses of R-CYVE [rituximab, cytarabine, and etoposide] and 2 courses of maintenance therapy [vincristine, cytarabine, doxorubicin, prednisone, and rituximab]).…”
Section: Initial Treatmentmentioning
confidence: 99%
“…These results are in contrast to the EFS and OS rates for dose-adjusted EPOCH-R reported in the aforementioned analyses, 31,32 and the survival rates reported in this phase II study are also inferior to those reported in the LMB2001 prospective study (discussed previously). 28 In the absence of data from randomized trials, optimal first-line treatment of patients with PMBL has not been established. Enrollment in a clinical trial is preferred for all patients.…”
Section: Pbcl-3mentioning
confidence: 99%
See 2 more Smart Citations